Using Non-Dominant Languages in Basic Education in Nepal: Major Issues, Challenges and Some Strategies - Regmi, Dan Raj (Nepalese Linguistics, 2025)
This paper investigates some major issues and challenges in using non-dominant languages (NDLs) in basic education in Nepal and proposes some strategies to meet those challenges. Analyzing both primary and secondary data employing qualitative approach within the perspective of transformative worldview, it has identified some major issues and challenges pertaining to orthography, language policy, language vitality, resources and funding. However, a perplexing tension, though empirically unfounded, between the desire for preserving NDLs and irresistible societal pressure for instant proficiencies in English and Nepali, has strongly debarred NDLs from being used in basic education resulting inequality, class repetition, high dropout and very low quality performance. To address such issues and challenges, the local governments have to frame a multilingual language policy; and local communities as well as experts have to work together following integrative approach to effectively bring NDLs into basic education for ensuring educational equality, quality and empowering the marginalized communities in Nepal.